PERLINDUNGAN HUKUM PERSAMAAN HAK ASASI PEREMPUAN DALAM MENINGKATKAN PEREKONOMIAN INDONESIA - Wiwik Sri Widiarty (to-ra, 2017)
Abstract The struggle of women in achieving equality and justice has been carried out long ago, whether in the economic, social, cultural, and political aspects, in fact it has not been able to raise the dignity of women to be equal to men. Various laws and regulations governing women's rights include those implied in the Convention on Elimination of All Forms Discrimination Againts Women (CEDAW), namely the rights possessed by a woman, both because she is a human being and as a woman. Even though CEDAW has been rati ed, there are still discriminatory regulations, such as the Investment Law, Marriage Law, the Law on Placement and Protection of Overseas Workers, the Citizenship Act, and other Regional Regulations. Therefore, legal protection of women's human rights is very important, for women whose rights have been violated, especially since there are many cases of female labor violence working to help improve the family economy abroad. Keywords: legal protection; women's human rights; female labor violence .